The German student movement and the literary imagination : transnational memories of protest and dissent - Rinner, Susanne (Protest, culture and society, 2013)
Introduction. Trans/national memories of 1968 -- Remember? 1968 in German fiction -- Forget it? 1968 in East Germany -- Transatlantic encounters between Germany and the United States as intercultural exchange and generational conflict -- Transnational memories: 1968 and Turkish-German authors -- Conclusion. Continued taboos, confirmed canons